Religious Leaders’ Views On Karaoke Entertainment At Walimatul ‘Urs Celebrations In Jekan Raya Subdistrict, Palangka Raya Village - Ahmad Juanda; Anas Maulana; Ahmad Sadiani (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2026)
This study examines the views of religious leaders on karaoke entertainment at the walimatul 'urs event in Jekan Raya District, Palangkaraya Village. The phenomenon of karaoke entertainment at weddings is increasingly being found and has generated various responses from religious leaders. The focus of the problem is 3, namely 1) The views of religious leaders on the appearance of karaoke groups at the Walimatul 'Urs event, namely Based on the results of the study, the views of religious leaders on the appearance of karaoke groups at the walīmatul 'urs event are divided into two, namely allowing with conditions in accordance with Islamic law and rejecting because it has the potential to cause harm. However, all religious leaders agree that the implementation of walīmatul 'urs must maintain Islamic values, ethics, and politeness. Therefore, acceptance of karaoke groups depends on the form of implementation and its suitability with the principles of Islamic law and prevailing norms in society. . 2) The bride and groom's family contracted a karaoke group for their child's wedding entertainment event is the decision of the bride and groom's family to contract a karaoke group at the walīmatul 'urs event is influenced by social, cultural factors, and the entertainment needs of the community. The presence of a karaoke group is seen as being able to enliven the event, entertain guests, and strengthen social ties. Despite differing views from religious leaders, the family still strives to adapt the implementation to religious norms. Thus, this decision represents a form of adaptation between community traditions, social needs, and Islamic values. 3) The activity of karaoke group performers in entertaining performances at Walimatul 'Urs events is essentially to entertain It also serves as a medium for social interaction that enlivens wedding celebrations. Public acceptance of these activities depends on their adherence to ethics, norms of decency, and the principles of Islamic law. Therefore, performers strive to adapt their performances to local culture so that the entertainment function aligns with prevailing religious values.